Combined Effects of Air Pollution and Changes in Physical Activity With Cardiovascular Disease in Patients With Dyslipidemia - Hye Jun Kim; Yun Hwan Oh; Sun Jae Park; Jihun Song; Kyuwoong Kim; Daein Choi; Seogsong Jeong; Sang Min Park (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Sedentary behavior elevates cardiovascular disease (CVD) risk in patients with dyslipidemia. Increasing physical activity (PA) is recommended alongside pharmacological therapy to prevent CVD, though benefits across environmental conditions are unclear. Methods and Results We analyzed data from 113 918 newly diagnosed patients with dyslipidemia (2009–2012) without prior CVD, sourced from the Korea National Health Insurance Service. Ambient particulate matter (PM) 2.5 and PM10 levels were collected from the National Ambient Air Monitoring System in South Korea. Changes in PA, measured in metabolic equivalents of task–min/wk before and after dyslipidemia diagnosis, were evaluated for associations with air pollution levels and CVD risk using Cox proportional hazards regression. Patients were followed from January 1, 2013, until CVD onset, death, or December 31, 2021. Among patients exposed to low to moderate PM2.5 levels (≤25 μg/m3), increasing PA from inactive to ≥1000 metabolic equivalents of tasks–min/wk was associated with a lower risk of CVD (adjusted hazard ratio, 0.82 [95% CI, 0.70–0.97]; P for trend=0.022). In high PM2.5 (>25 μg/m3) conditions, increasing PA from inactive and decreasing PA from ≥1000 metabolic equivalents of task–min/wk was associated with reduced (P for trend=0.010) and elevated (P for trend=0.028) CVD risks, respectively. For PM10, increased PA was linked to reduced CVD risk (P for trend=0.002) and decreased PA to elevated risk (P for trend=0.042) in low to moderate PM10 (≤50 μg/m3) conditions, though benefits diminished at high PM10 (>50 μg/m3) exposures. Conclusions Promoting PA, while considering the high potential cardiovascular risk associated with air pollution, may be an effective intervention against CVD in patients with dyslipidemia.